2004
DOI: 10.1023/b:boun.0000039372.86053.ff
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Advection on the Short Term CO 2 -Budget in and Above a Forest Canopy

Abstract: Abstract. An experimental micrometeorological set-up was established at the CARBOEU-RO-FLUX site in Tharandt, Germany, to measure all relevant variables for the calculation of the vertical and horizontal advective fluxes of carbon dioxide. The set-up includes two auxiliary towers to measure horizontal and vertical CO 2 and H 2 O gradients through the canopy, and to make ultrasonic wind measurements in the trunk space. In combination with the longterm flux tower an approximately even-sided prism with a typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
161
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(170 citation statements)
references
References 26 publications
8
161
0
1
Order By: Relevance
“…It is difficult to explore these processes via single tower measurements, though some theoretical and experimental attempts are presented in Assouline et al (2008) for heat and water vapour above small reservoirs. Recent studies (Feigenwinter et al 2004;Aubinet et al 2005;Sun et al 2007) found that advection may be significant even during daytime especially with low intensity turbulence. However, the main concern refers to nocturnal conditions when an underestimation of CO 2 fluxes using the eddy-covariance technique frequently occurs because non-turbulent transport processes, not taken into account by the eddy-covariance system, become significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult to explore these processes via single tower measurements, though some theoretical and experimental attempts are presented in Assouline et al (2008) for heat and water vapour above small reservoirs. Recent studies (Feigenwinter et al 2004;Aubinet et al 2005;Sun et al 2007) found that advection may be significant even during daytime especially with low intensity turbulence. However, the main concern refers to nocturnal conditions when an underestimation of CO 2 fluxes using the eddy-covariance technique frequently occurs because non-turbulent transport processes, not taken into account by the eddy-covariance system, become significant.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that departures from MOST scaling for FV may provide additional clues as to when CO 2 advection is important. However, Feigenwinter et al 2004, Aubinet et al 2005, Sun et al 2007 do not discuss the role of advection on FV similarity functions (only on CO 2 fluxes via the mean scalar continuity).…”
Section: Discussionmentioning
confidence: 99%
“…Half hourly means of the measured variables were used further for the calculations, following both Feigenwinter et al (2008), where the same data were analysed, and other studies for FLUXNET sites (e.g., Feigenwinter et al, 2004;Aubinet et al, 2005;Heinesch et al, 2007;Turnipseed et al, 2004, Staebler andFitzjarrald, 2004;Yi et al, 2008).…”
Section: Procedures To Calculate the 3-d Fields Of The Physical Quantmentioning
confidence: 99%
“…Goulden et al, 1996;Suyker et al, 2005;Moureaux et al, 2006;Zhao et al, 2006); and (ii) the "correction approach", based on a direct estimation of all the CO 2 balance terms, including the advection terms (e.g. Aubinet et al, 2003Aubinet et al, , 2005Feigenwinter et al, 2004;Staebler and Fitzjarrald, 2004;Marcolla et al, 2005;Sun et al, 2007;Yi et al, 2008;Montagnani et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In this context, advection is a highly discussed topic especially in relation to the net ecosystem exchange of CO 2 (e.g. Aubinet et al 2003;Baldocchi et al 2000a;Feigenwinter et al 2004;Lee 1998;Lee and Hu 2002;Paw U et al 2000;Staebler and Fitzjarrald 2004). It is also suspected and discussed that advection may contribute to the lack of energy closure (e.g.…”
Section: Introductionmentioning
confidence: 99%